Challenges of the illicit crops substitution program: the case of the municipality of Valle del Guamuez, Colombia - Miguez-Lopez, Fredy Alexander; Alba-Maldonado, José Manuel (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article aims to describe the accounts of farmers, collectors, and community social leaders regarding the impact of the Comprehensive National Program for the Substitution of Illicit Crops (PNIS for its acronym in spanish) on social, economic, environmental, and institutional issues in Valle del Guamuez Municipality, Putumayo, Colombia. The research approach is qualitative, employing a comprehensive hermeneutic method, and the textual sources of information include the narratives of four cultivators, collectors, and social leaders from the region. The achieved results are presented under four analytical categories: social, economic, environmental, and institutional. Among the main findings, it is highlighted that, according to the accounts, the PNIS has not had a significant impact on improving the conditions of the communities affected by coca crops, primarily due to the non-compliance of certain commitments by the government and program beneficiaries.